Evaluation of Online Learning in the Covid-19 Era Through the Office 365 Program at SMP Negeri 5 Leihitu, Central Maluku Regency - Rudolf Kempa; Siti Ramla Ollong; Vando Kristi Makaruku (Peneliti.net, 2022)
With the government's prohibition on face-to-face learning, schools from the elementary school to university levels are looking for alternative learning that is in accordance with the current covid pandemic conditions. Online learning is an alternative that is considered effective, where this learning utilizes internet technology in managing learning with a wider reach. By implementing online learning, we must pay more attention to the selection of application programs that are in accordance with the conditions and needs in learning. Office 365 is considered capable of accommodating learning needs during the current pandemic given the various advantages it has, but there are still weaknesses and obstacles that we need to examine so that learning can be effective and efficient even though it is carried out online and is able to improve students' academic and non-academic achievements. This study aims to evaluate online learning programs in the Covid-19 era through the Office 365 at SMP Negeri 5 Leihitu, Central Maluku. The research is a descriptive evaluation study with a qualitative approach and the CIPP evaluation model with the research subjects being the principal, vice principal for curriculum affairs, deputy principal for student affairs, and three senior teachers and 2 teachers. Data collection uses interview, observation and documentation techniques, while data analysis uses data reduction techniques, data presentation and ends with conclusion drawing or data verification. Based on the results of online learning evaluation research through Office 365 , it was found that in reality there were still facilities and infrastructure that were not yet available, the human resources for teachers and students were not adequate. However , learning can be carried out well , supported by competent operators and support from schools and parents.